Counterintuitive findings from a qualitative study of mental health in English women's prisons. Issue 4 (19th December 2016) - Caulfield, Laura S.
Abstract : Purpose: Large numbers of women in prison report significant emotional and mental health problems, and there is evidence to suggest that the prison environment may exacerbate the incidence and severity of these issues (Armour, 2012). However, there has been limited exploration of the extent to which women's mental health problems exist prior to incarceration, whether symptoms first occur in incarceration, and how incarceration affects this. The paper aims to discuss these issues. Design/methodology/approach: In-depth interviews were conducted with 43 women incarcerated in three English prisons and a thematic analysis of the data was conducted. Review of official prison records provided a form of data triangulation. Findings: Analysis of the data revealed that while many women who experienced mental health issues in prison had experienced these issues in the past, a number of women reported first experiencing mental health and emotional problems only after entering prison. Although these problems often recede, this demonstrates the significant impact that entering prison can have upon the mental health of women. Unusually, the data highlighted many positive experiences of support within prison. However, there was some lack of consistency in the treatment and support offered to women. Originality/value: The data presented here are in many ways more positive than previous research and – as opposed to much of the existing literature that simply states the prevalence women's issues in prison – provides insight into the lived experiences of women in prison. This paper documents how prison can present an opportunity for women to engage with treatment, but there is a need for a clearer understanding of women's needs and consistent and appropriate support.